The 80x86 IBM PC & compatible computers volumes I & II : assembly language, design and interfacing - Mazidi, Muhammad Ali (Prentice Hall, 1995)
This text covers IBM/IBM compatible microprocessors. It provides an introduction for computer users who need to become expert in the 80X86 family. The reader is guided by the step-wise format through each phase of assembly language programming and hardware aspects of the Intel family.